Milled Crown on Post Crack Tooth Syndrome as the Denture Abutment Tooth: A Case Report - Sarah Sabrina Mahalil Amin; Muhammad Annurdin Sabarudin; Nusima Mohamed; John Chong Keat Hon; Wan Nor Syariza Wan Ali (Cureus, Inc., 2024)
Indexed by WOS/ERA